2016
DOI: 10.1021/acs.joc.6b01693
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Homoneryl and Homogeranyl Triazole Bisphosphonates

Abstract: Isoprenoid-substituted bisphosphonates are known to serve as inhibitors of the enzyme geranylgeranyl diphosphate synthase, and their activity can be highly sensitive to olefin stereochemistry. A mixture of homogeranyl and homoneryl triazole bisphosphonates has previously demonstrated potent activity, and thus stereocontrolled syntheses of the individual isomers have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…[ 14 C]-IPP was purchased from American Radiolabeled Chemicals (St. Louis, MO). The pure homogeranyl and homoneryl triazole bisphosphonates (7 and 8) and the 3:1 (HG:HN) mixture (6) were prepared as previously reported (Wills et al, 2015;Matthiesen et al, 2016). Stock solutions (50 mM) of the triazole bisphosphonate sodium salts were prepared in sterile water and stored at 220°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 C]-IPP was purchased from American Radiolabeled Chemicals (St. Louis, MO). The pure homogeranyl and homoneryl triazole bisphosphonates (7 and 8) and the 3:1 (HG:HN) mixture (6) were prepared as previously reported (Wills et al, 2015;Matthiesen et al, 2016). Stock solutions (50 mM) of the triazole bisphosphonate sodium salts were prepared in sterile water and stored at 220°C.…”
Section: Methodsmentioning
confidence: 99%
“…1) was identified as the most potent inhibitor of GGDPS described to date with an IC 50 of 45 nM (Wills et al, 2015). Given the relative activities of the geranyl/neryl isomers, one might predict that the homoneryl isomer would be significantly more potent than the homogeranyl isomer, and efforts have therefore been focused on the preparation of the pure isomers (Matthiesen et al, 2016). Here we present our findings for the biologic activities of the homogeranyl and homoneryl triazole bisphosphonates and demonstrate that these compounds interact in a synergistic manner to inhibit GGDPS, thus establishing a new paradigm for the development of GGDPS inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the ratio of olefin isomers was determined from the average integration of resonances corresponding to the sp 2 olefin carbons (137.7 and 133.7 ppm for the Z -isomer and 137.6 and 133.5 ppm for the E -isomer) and the adjacent methylene group (31.1 ppm for the Z -isomer and 38.9 ppm for the E -isomer) in the 13 C NMR spectrum. 11 The 13 C NMR spectrum of the geranyl-derived triazole 17b indicated that this analogue was a single isomer within the limits of detection.…”
Section: Synthesismentioning
confidence: 99%
“…The ratio was determined by integration of the resonances at 32.1 and 39.9 ppm, which correspond to the methylene carbon at C-6. 11,22 Because the E -isomer was such a minor component, the mixture was carried forward. The primary alcohols then were allowed to react with MsCl and Et 3 N followed by LiBr to afford the corresponding bishomoallylic bromides 13a , 23 13b , 24 and 13c in low to moderate yields.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation